Beyond Oman’s shores: records of Oxyurichthys omanensis (Teleostei: Gobiidae) from the central and southern regions of the Western Indian Ocean - Zarei, Fatah; Jufaili, Saud M. Al; Béarez, Philippe; Ponton, Dominique; Pruvost, Patrice; Chakona, Albert (Zootaxa, 2025)
The goby genus Oxyurichthys (Gobionellinae) currently comprises 21 recognized species distributed across the tropical Indo-West Pacific region, with 12 species inhabiting the Western Indian Ocean (WIO). A recent examination of specimens from a mudflat habitat in northern Oman, located in the northwestern Indian Ocean, led to the description of a new species, Oxyurichthys omanensis. In this study, we re-examined collections of Oxyurichthys specimens from the central and southern WIO, previously identified as O. ophthalmonema. Our results provide robust evidence for the presence of O. omanensis in these regions, specifically from Kenya, Mayotte, and Madagascar. Here, we present a detailed morphological assessment of genotyped voucher specimens, enhanced by comprehensive descriptive information to further clarify the identification and distribution of Oxyurichthys species in the central and southern WIO.